2022
DOI: 10.1371/journal.pone.0271133
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control risk factors in health workers infected with SARS-CoV-2 in Jordan: A case control study

Abstract: Background Despite under-reporting, health workers (HWs) accounted for 2 to 30% of the reported COVID-19 cases worldwide. In line with data from other countries, Jordan recorded multiple case surges among HWs. Methods Based on the standardized WHO UNITY case-control study protocol on assessing risk factors for SARS-CoV-2 infection in HWs, HWs with confirmed COVID-19 were recruited as cases from eight hospitals in Jordan. HWs exposed to COVID-19 patients in the same setting but without infection were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The evolution of the pandemic in Jordan confirmed the forecasting provided by the modeling exercise and helped confirm the effectiveness of the policy adopted by the government of Jordan. The insights from scenario-based modeling influenced the implementation of PHSMs and PDIs; specifically, scenario-based models were used to updating PHSM and PDI guidelines in addition to other evidence-based actions, such as infection prevention and control (33). The scenario is defined by 2 key parameters: coverage and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of the pandemic in Jordan confirmed the forecasting provided by the modeling exercise and helped confirm the effectiveness of the policy adopted by the government of Jordan. The insights from scenario-based modeling influenced the implementation of PHSMs and PDIs; specifically, scenario-based models were used to updating PHSM and PDI guidelines in addition to other evidence-based actions, such as infection prevention and control (33). The scenario is defined by 2 key parameters: coverage and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The webinar was held on 13 January 2023 and brought together 55 healthcare professionals from hospitals and primary healthcare centres across all governorates in Jordan as well as experts from MoH, JCDC and other partners. The information provided on electrolyte and fluid management, intensive care, the setup of treatment centres for infectious diseases and IPC can be applied for diseases beyond cholera 36. A partnership between WHO and the MoH Hospital Administration has since been established and organises webinars for healthcare providers, including on airway and trauma management.…”
Section: Sustainable Strengthening Of Capacitiesmentioning
confidence: 99%
“…The information provided on electrolyte and fluid management, intensive care, the setup of treatment centres for infectious diseases and IPC can be applied for diseases beyond cholera. 36 A partnership between WHO and the MoH Hospital Administration has since been established and organises webinars for healthcare providers, including on airway and trauma management.…”
Section: Sustainable Strengthening Of Capacitiesmentioning
confidence: 99%
“…A case-control study was done in Jordan and confirmed the role of hand hygiene as one of the most cost-effective measures to combat the spreading of viral infections [ 3 ].…”
Section: Editorialmentioning
confidence: 99%